The Influence of Viral Marketing and Celebrity Endorser On The Purchase Intention of Skintific Products In Tanjungpinang - Septi Haryani, Dwi; Yulius, Yudi; Limakrisna, Nandan (Green Publisher, 2023)
In the cosmetics industry, the use of viral marketing strategies and celebrity endorsers has been widely used to increase buying interest. Many studies have proven that buying interest is influenced by viral marketing strategies and celebrity endorsers. For this reason, this study aims to determine the influence of viral marketing and celebrity endorsers on the interest in buying Skintific products in Tanjungpinang. The sample in this study was 384 respondents taken from the people of Tanjungpinang city who had an interest in cosmetics. The research method used in this study is quantitative research with questionnaire distribution and using multiple linear regression analysis. The results showed that viral marketing and celebrity endorsers had a positive and significant effect on the purchase intention of Skintific products in Tanjungpinang. Several recommendations and managerial implications have been proposed at the end of this study.